HUMAN FREEDOM IN THE SOPHIOLOGY - Troino-Funtusova, N. V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2016)
The article deals with place of the person in the Unity system on the example of Russian sophiology. The understanding of the concept of human freedom in the philosophical system of V. Solovyov, S. Bulgakov, P. Florensky, E. Trubetskoy is analyzes. Reveals the concept of human freedom through the concept of identity. The question about the possibility of personal freedoms in the Russian sophiology is posted and the problematic of freedom in terms of the Christian position is demonstrated. The idea of Sophia breaks the connection between man and Christ as the source of freedom.